FAKTOR-FAKTOR YANG MEMENGARUHI IBU DALAM PENGGUNAAN ALAT KONTRASEPSI BAWAH KULIT (AKBK) DI PUSKESMAS PB SELAYANG II KOTA MEDAN - sari, sonia novita; Razia Begum Suroyo; Nuriah Arma (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
An effective contraception program is the Long Term Contraceptive Method with an under skin contraceptive device. This study aimed to determine the factors that affect mothers in using implant contraception at PB Selayang II Health Center, Medan City. This is a mixed method research with an explanatory approach. The quantitative design usesd cross sectional, the qualitative design used a narrative approach. The population was all mothers at Working Area of PB Selayang II Health Center amount 13,119 mothers, with a quantitative sample of 99 mothers, for a qualitative sample of 3 mothers, 1 midwife, 1 ustadz. Quantitative data analysis used univariate, bivariate and multivariate analysis. Qualitative analysis used familiarization analysis, identifying thematic framework, indexing, charting, imaging and interpretation. The results of this study indicate that there was an influence of the variables of health workers role, beliefs, socio-culture, infrastructure, side effects, economy, and mother's activities on the use of implant contraception at the Health Center. The most dominant factor was the mother’s activity. Qualitatively, the most influencing factor was the mother's activity. The conclusion shows that there is an influence of health workers role, beliefs, socio-culture, infrastructure, side effects, economy, and mother's activities on the use of implant contraception at PB Selayang II Health Center Medan City. It is suggested for mothers to take part in counseling activities carried out by health workers, and then health workers are expected to make home visits to provide explanations to mothers about the effectiveness of using implant contraception.